Limitations of the Integrated Development Plan as a public participation tool in decision making in Dr Kenneth Kaunda District Municipality - Ramone, Tebogo Sarah (University of the Witwatersrand, Johannesburg, 2023)
This study examines the limitations of the Integrated Development Plan as a tool for public engagement in decision-making within the context of the Dr Kenneth Kaunda District Municipality. The study is grounded in the People Centred Development Theory, which emphasizes the participation of all stakeholders in the development process. The study employs a case study research design and qualitative methodology, with data gathered through interviews and document analysis. The findings reveal that the IDP plays a significant role in facilitating service delivery within the municipality. It serves as a guideline for identifying needs, setting priorities, and implementing strategies to enhance service provision. The IDP also fosters stakeholder participation and enables continuous reporting, thereby promoting inclusive development. However, several limitations in the IDP process were identified. Public participation was inconsistent, with meetings often held during working hours, excluding many community members. This lack of inclusivity resulted in the underrepresentation of diverse perspectives in decision-making. Moreover, certain critical sector departments did not participate, hindering integrated development goals. Communication and induction processes were also lacking, with stakeholders and communities not effectively engaged or informed. Beyond the planning aspect, the study also identified challenges in the implementation of the IDP. These challenges ranged from limited funding, lack of skilled personnel, limited community interest, duplication of processes and projects, and a lack of political will and effective leadership. The inadequate resource allocation led some projects being unimplemented. To address the limitations identified, the study recommends comprehensive awareness campaigns to educate the public about the IDP, increased accessibility through multiple languages and digital platforms, and the use of diverse engagement methods. It also suggests aligning municipal objectives with the IDP, utilizing the Ward Development Plan, conducting IDP Representative Forum meetings, improving communication and recruitment practices, effectively utilizing scarce resources, and increasing the tenure of the IDP.
This research is submitted in fulfillment of the requirements for the Master of Management. to the Faculty of Commerce, Law and Management, School of Governance, University of the Witwatersrand, Johannesburg 2023
Keywords: Integrated Development Plan; Public Participation; and Service Delivery; SDG-8: Decent work and economic growth